Halal Digital Ecosystem and Sustainable Growth: Challenges in the Global Market (Proceeding of the International Conference on Economics, Accounting, and Taxation, 2025)
The intersection between digital transformation and the halal economy has created new pathways for sustainable global development. This study explores how the Halal Digital Ecosystem (HDE)—an integrated network of producers, certifiers, regulators, and consumers—contributes to sustainable growth by aligning digital innovation with Islamic ethical principles. Employing a mixed-method explanatory sequential design, the research combines quantitative analysis using Structural Equation Modeling–Partial Least Squares (SEM–PLS) with qualitative interviews involving policymakers, halal entrepreneurs, and certification authorities from Indonesia, Malaysia, and GCC countries. The findings reveal that digital infrastructure readiness and certification transparency significantly influence sustainable growth, while innovation capability acts as a mediating factor that strengthens the relationship between digitalization and sustainability outcomes. Qualitative insights highlight persistent challenges, including fragmented cross-border governance, limited digital literacy among halal SMEs, and the absence of harmonized certification standards. These barriers indicate that achieving sustainability requires not only technological advancement but also ethical and institutional alignment based on maqāṣid al-sharī‘ah. The study introduces the Halal Digital Ecosystem–Sustainability (HDE–S) Framework, providing both theoretical and practical contributions to the literature on sustainable digital economies. Policy implications emphasize the need for integrated halal digital governance, capacity building, and regional collaboration to enhance competitiveness, inclusivity, and ethical compliance in the global halal market.